RELATIONSHIP OF COMPARATIVE LINGUISTICS WITH OTHER FIELDS - To`lqinova Charos Davron qizi; Abdurahmonova Zilola Yoqubjon qizi (Ta’lim innovatsiyasi va integratsiyasi, 2023)
Abstract : The field of comparative linguistics plays a crucial role in understanding the relationships between different languages and their historical development. This paper aims to explore the interconnections between comparative linguistics and other related fields, such as anthropology, archaeology, cognitive science, and computer science. It discusses how comparative linguistics contributes to our understanding of human history, migration patterns, and cultural evolution through the examination of language similarities and differences. Furthermore, the paper also investigates the role of comparative linguistics in the development of artificial intelligence, natural language processing, and machine translation. By examining the relationship between comparative linguistics and these diverse fields, this paper highlights the interdisciplinary nature of linguistics and its significance in various aspects of human knowledge and technology.